Changes of Structural and Functional Attention Control Networks in Subclinical Hypothyroidism - Yin, Jingjing; Xie, Lei; Luo, DongXue; Huang, Jinzhuang; Guo, Ruiwei; Zheng, Yanmin; Xu, Wencan; Duan, Shouxing; Lin, Zhirong; Ma, Shuhua (Frontiers in Behavioral Neuroscience, 2021)
Objective: The present study aimed to explore the structural changes in subclinical hypothyroidism (SCH) patients using voxel-based morphometry (VBM), and to investigate the altered attentional control networks using functional magnetic resonance imaging (fMRI) during the performance of a modified Stroop task with Chinese characters. Methods: High resolution 3D T1-weighted images and an fMRI scan were taken from eighteen patients with SCH and 18 matched control subjects. The Montreal Cognitive Assessment Chinese-revised and Stroop task were used to evaluate the cognitive and attention control of the participants. Results: Compared to controls, the VBM results showed decreased grey matter volumes in the bilateral prefrontal cortices (PFCs, including middle, medial and inferior frontal gyri), cingulate gyrus, precuneus, left middle temporal gyrus and insula in SCH patients. The fMRI results showed a distributed network of brain regions in both groups, consisting of prefrontal cortices (including superior and middle and inferior frontal cortices), anterior cingulate cortex (ACC), posterior cingulate cortex, and precuneus, as well as the insula and caudate nucleus. Compared with controls, the SCH group had lower activation of the above brain areas, especially during the color-naming task. In addition, the normalized gray matter volume (nGMV) was negatively correlated with thyroid stimulating hormone (TSH) level (r=-0.722, p<0.001). Conclusion: Results indicate that patients with SCH exhibit reduced gray matter volumes, altered bold signals and activation in regions associated with attention control, which further suggest that SCH patients may have attentional control deficiency, and the weakened PFC-ACC-precuneus brain network might be one of the neural mechanisms. Negative correlations between nGMV and TSH suggest that TSH elevation may induce abnormalities in the cortex.